2018
DOI: 10.3892/ol.2018.7727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective inhibition of aquaporin 1 on chemotherapy sensitivity of J82 human bladder cancer cells

Abstract: Abstract. The occurrence of resistance to mitomycin C (MMC) often limits its clinical effectiveness. Combination therapy thus is employed to overcome this treatment resistance. The present study aimed to establish a novel J82 bladder cancer cell line so as to study the effect of inhibition of aquaporin 1 (AQP-1) on chemotherapy sensitivity of J82 bladder cancer cells. A novel J82 bladder cancer cell line whose expression of AQP-1 is inhibited was established through transfection of J82 cells with newly constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Investigating the mechanism regulating chemosensitivity uncovered that cytoplasmic AQP1 and glycogen synthase kinase-3b (GSK3b) interact via 12 armadillo repeats of bcatenin, leading to b-catenin accumulation and its interaction with Topo IIa and enhancing its activity, which increased the sensitivity to anthracycline treatment (91). This association with chemotherapy sensitivity via AQP1 occurred not only in breast cancer but also in human bladder cancer cells, where AQP1 inhibition enhanced mitomycin C sensitivity, and also in colorectal and ovarian cancers (130)(131)(132).…”
Section: Aqp1mentioning
confidence: 99%
“…Investigating the mechanism regulating chemosensitivity uncovered that cytoplasmic AQP1 and glycogen synthase kinase-3b (GSK3b) interact via 12 armadillo repeats of bcatenin, leading to b-catenin accumulation and its interaction with Topo IIa and enhancing its activity, which increased the sensitivity to anthracycline treatment (91). This association with chemotherapy sensitivity via AQP1 occurred not only in breast cancer but also in human bladder cancer cells, where AQP1 inhibition enhanced mitomycin C sensitivity, and also in colorectal and ovarian cancers (130)(131)(132).…”
Section: Aqp1mentioning
confidence: 99%
“…Their findings demonstrated the potential significance of AQP1 to guide bladder carcinoma diagnosis and treatment. Furthermore, Zhang et al (15) reported that selective inhibition of AQP1 enhanced the sensitivity of J82 BCa cells to mitomycin C. Moreover, AQP3, AQP4, AQP7, AQP9, and AQP11 transcripts were detected in both freshly isolated urothelial cells and cultured urothelial cells. At the protein level, an unequivocal expression of AQP3 was also observed, with immunohistochemistry revealing intense staining of cell membranes in both the basal and intermediate layers of normal bladder urothelial tissue (10).…”
Section: Discussionmentioning
confidence: 99%
“…It's worth noting that most studies show that AQP1 gene acts as an oncogene in various solid cancers to promote cancer development (12)(13)(14), whereas only a few studies report AQP1 as a tumor suppressor that inhibits tumor growth (21,58). Recently, Marietta Tan et al also showed that AQP1 was epigenetically downregulated by promoter methylation and was associated with improved prognosis in salivary gland adenoid cystic carcinoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…facilitates transcellular water transportation (11). AQP1 plays an oncogenic role in many types of solid cancer, including colorectal cancer, breast cancer, bladder cancer (12)(13)(14). Functionally, AQP1 regulates cell proliferation, invasion, metastasis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%